Stability of Acid Black 210 dye in Tannery Industry Effluent in Aqueous Solution Is Limited and Generates Harmful Subproducts - Christovam, Elisa Maria; Franco, Jefferson Honorio; Zocolo, Guilherme Julião; Fusco Almeida, Ana Marisa; Marcelino, Monica Yonashiro; de Oliveira, Danielle Palma; Boldrin Zanoni, Maria Valnice (Frontiers in Environmental Science, 2022)
The present work investigates the occurrence of the Acid Black 210 (AB210) dye and its subproducts in the tannery industry by analytical techniques. The AB210 is an important dye characterized by three azo groups as a chromophore and is one of the most used azo dyes in the tannery industry. The stability of AB210 in front of chlorination, sunlight exposition, and ambient conditions was investigated, as well as its occurrence and degradation products in the tannery wastewater. The stability study of AB210 showed a decrease in dye concentration of up to 45 % after 14 days at room temperature. The exposure of the AB 210 by a solar simulator for 3 hours showed discoloration of the dye. Furthermore, the chlorination of the AB210 caused a reduction of 25% in the intensity of the absorption band at the visible region after 300 s of treatment with sodium hypochlorite (NaClO). Studies based on high-performance liquid chromatography (HPLC-DAD), liquid chromatography-mass spectrometry (LC-MS/MS), and nuclear magnetic resonance (NMR) have indicated the occurrence of several harmful compounds such as benzene, cresol, naphthalene, phenol, 2-naphthylamine, and phenylacetic acid, and three aromatic amines, 2-naphthylamine, 2,6-dimethylaniline and 4-nitroaniline from the tannery industry. The cytotoxicity assay showed toxicity for the samples stored for a long period. Thus, the immortalized human keratinocyte (HaCAT) and 3T3 cells assays for the AB210 stored for 14 days showed 70 % cell death in both strains evaluated. Our results demonstrated that the AB210 degradation is a great environmental concern due to increased toxicity for the body of living beings, especially for humans, as their biotransformation produces harmful compounds such as amines, which have been widely condemned by the International Agency for Research on Cancer. Keywords: Acid Black 210 dye; analysis of tannery industry wastewater; degradation of leather dye, evaluation of tannery effluent.